2020
DOI: 10.7764/ijanr.v47i3.2241
|View full text |Cite
|
Sign up to set email alerts
|

Diversifying European agricultural systems by intercropping

Abstract: Cropping system diversification is a key factor in developing more sustainable cropping and food systems. The agroecological practice of intercropping, meaning the simultaneous cultivation of two or more species in the same field, has recently gained renewed interest as a means of ecological intensification in European agricultural research. We discuss some recent research developments regarding 1) intercropping for ecological intensification in agroecological and conventional cropping systems, 2) studies on n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 48 publications
(68 reference statements)
0
10
0
Order By: Relevance
“…Sunflower intercropping with alfalfa proved the most appropriate and stable yields than sole cropping [49]. Similarly, intercropping may contribute to the mitigation of climate change, for example, by reducing the need for fossil-based N fertilizer, mechanical weed control, and the associated N 2 O and CO 2 emissions [11]. Legumes used in intercropping and doubled-up legume technology reduce reliance on nitrogen fertilizer and pesticide inputs then lower the GHG emission [39].…”
Section: Intercropping and Yield Stabilitymentioning
confidence: 99%
See 2 more Smart Citations
“…Sunflower intercropping with alfalfa proved the most appropriate and stable yields than sole cropping [49]. Similarly, intercropping may contribute to the mitigation of climate change, for example, by reducing the need for fossil-based N fertilizer, mechanical weed control, and the associated N 2 O and CO 2 emissions [11]. Legumes used in intercropping and doubled-up legume technology reduce reliance on nitrogen fertilizer and pesticide inputs then lower the GHG emission [39].…”
Section: Intercropping and Yield Stabilitymentioning
confidence: 99%
“…One possible approach would be a diversification cropping system that is a key factor in developing a more sustainable agroecological system [1]. A key agroecological principle in agricultural production systems is diversification in time (rotation) and space (intercropping, agroforestry systems, biofertilizers, and cover crops) via mechanisms of competition, facilitation, complementarity, and compensation [11], which lies in how much diversified the agro-production system is and the positive interaction among the diverse components of the system [12,13]. Multispecies cropping systems can significantly reduce fertilizer overuse problems thereby minimizing the environmental impacts of agriculture while maintaining high food production [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intercropping systems have been widely applied worldwide due to their high economic benefits and land-use efficiency 27 , e.g., in Germany 30 , China 31 , and Brazil 32 . Several studies have shown that compared to monocropping, crop diversification and intercropping can effectively increase the resistance and resilience of agroecosystems to drought and disease incidences 33 , reduce the risk of crop loss 34 , reduce the use of external fertilizers, increase soil fertility 35 , optimize plantation structure 36 , improve land use efficiency 35 , and improve water use efficiency, nitrogen use efficiency, and field productivity 37 , 38 .…”
Section: Introductionmentioning
confidence: 99%
“…Mixed cropping is a sustainable agricultural practice used all over the world to make a very efficient use of resources [ 1 ]. Most of the studied is legumes and cereals mixed cultivation systems [ 2 , 3 , 4 ]. This leads to improved utilisation of environmental resources such as light, water and nutrients [ 5 , 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%